Handbook of research on security considerations in cloud computing - Munir, Kashif, 1976-; Al-Mutairi, Mubarak S., 1971-; Mohammed, Lawan Ahmed, 1968- (IGI Global, 2015)
"This book brings together discussion on current approaches to cloud-based technologies and assesses the possibilities for future advancements in this field by highlighting the need for consumers to understand the unique nature of cloud-delivered security and to evaluate the different aspects of this service to verify if it will meet their needs"--Resumé vydavatele
Keywords: cloud computing; počítačová bezpečnost; computer security; příručky; elektronické knihy; handbooks and manuals; electronic books